Implementasi Manajemen Risiko Berbasis Syariah di Lembaga Keuangan: Analisis Komprehensif - Santoso, Budiyono (FADZAT: Jurnal Ekonomi Syariah, 2024)
Shariah-based risk management is a unique approach in Islamic financial institutions (IFIs) that integrates Shariah principles to manage risk effectively. This article presents an in-depth analysis of the concept, implementation process, case studies, challenges, role of technology, impact of the COVID-19 pandemic, governance, key performance indicators (KPIs), and future trends such as sustainability and artificial intelligence (AI). The literature review shows that Shariah risk management not only ensures Shariah compliance but also enhances financial stability and stakeholder confidence. Challenges such as lack of standardization and expertise can be addressed through regulation, education, and technology. This article is expanded to approximately 7,000 words with 15 references in APA 7th edition style.